Christian education as humanistic education? Opportunity and challenge within the secularized culture - Giuseppe Mari (Forum Pedagogiczne, 2017)
There is a strong and original relationship between Christian faith and Humanism, but it is necessary not to reduce the Christian education to Humanism. In fact, it was the Christian faith which gave birth to Humanism, not vice versa. It is necessary to put the distinction in order to avoid the reduction of the Christian education to the generic philanthropy. The Christian faith is, first of all, an encounter with Jesus, not only from the existential point of view, but also as a peculiar knowledge through Christ as God’s Word.